Pancreatic adenocarcinoma presenting as biliary sepsis in a young female: a case report highlighting diagnostic challenges and management strategies - Bhardwaj, Krishn Kant; Moolchandani, Pradeep Kumar; Saigal, Saurabh (International Journal of Advances in Medicine, 2025)
Pancreatic malignancy is typically associated with advanced age, with the highest incidence occurring globally in the 6th to 7th decade of life and a higher prevalence in men than women. We present a case of pancreatic adenocarcinoma in a 19-year-old female who presented with obstructive jaundice complicated by biliary sepsis, septic shock, and severe acute respiratory distress syndrome (ARDS). Management involved initiating broad-spectrum antibiotics and performing percutaneous transhepatic biliary drainage (PTBD) for source control. With gradual improvement, she was weaned off vasopressor and ventilator support and subsequently extubated. Magnetic resonance cholangiopancreatography (MRCP) revealed an ulcer proliferative growth, prompting endoscopic retrograde cholangiopancreatography (ERCP) with biopsy, which confirmed moderately differentiated adenocarcinoma of the pancreas. Pancreatic cancer, particularly ductal carcinomas, are rare in younger individuals, often leading to underappreciation of their clinical features and treatment among physicians. This case emphasizes the importance of considering malignancy in young patients presenting with pancreatic biliary sepsis. High suspicion warrants MRCP, and if malignancy is suspected, ERCP with histopathology should be performed for early diagnosis and intervention to impede disease progression.